Characteristics of Combination Shark Liver Oil (Centrophorus sp.) And Spirulina Powder as Food Supplement - Julian Franklin Soselisa; Sugeng Heri Suseno; Iriani Setyaningsih (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
The content of fish oil supplements is sufficient to fulfill the need of EPA and DHA, however adding nutritional value will be beneficial. This study was aimed to characterize the chemical content of the supplement from a combination of shark liver oil and Spirulina powder. The oil was extracted using dry rendering method at 50oC for 8 hours. The extracted oil was then combined with Spirulina powder with a concentration of 10; 30; and 50%. In general, the chemical characteristics of fish oil were affected by the addition of Spirulina plantesis. The fish oil with adddition of Spirulina 50% had the highest protein (24.3%) and essential amino acid content (but comparable DHA content. In conclusion, addition of Spirulina increased the chemical content of the fish oil, but reduced their fatty acid content.